The changing face of ethics – Developing a Code of Ethics for Professional Accountants from 1977 to 2006. (November 2018) - Sonnerfeldt, Amanda; Loft, Anne
This article aims to contextualise the development of the Code of Ethics for Professional Accountants by the International Federation of Accountants (IFAC) between 1977 and 2006. Drawing on transnational regulation literature, an extensive review of archival documents was conducted. The analysis unfolds the development of the Code in an increasingly complex regulatory environment, revealing the dynamic forces and sequence of events that influenced its nature and contents over three distinctive periods. This study reveals that the shifts in IFAC's priorities in pursuit of its global aspirations created mechanisms that allowed transnational accounting firms and international regulators to influence the priorities of the Ethics Committee. The Committee's efforts to legitimise and secure endorsement of the Code were constrained by its initial work programme to develop a model code through minimum harmonisation. Later, the Committee redirected its focus towards meeting the needs of the international regulators by adding more rule-based guidance within the principle-based Code and heavily prioritising independence.